Characterization of essential oils from odoriferous resins of Amazonian species of Protium Burm. f. (Research, Society and Development, 2022)
The odoriferous resins produced by the trees of Protium spp (Burseraceae) are known in the Amazonian region as “breus” where they have been used to caulk canoes, as a mosquito repellent, and also have potential use in perfumery. Most species in this region have had the essential oils of their resins characterized, thus, the objective of this study was to evaluate for the first time the volatile constituents from the resin of Protium gallosum Daly, P. paniculatum Engl., P. pillosum (Cuatrec.) Daly and P. paniculatum var. riedelianum (Engl.) Daly. The samples from the individuals that had been previously identified were collected at the Adolpho Ducke Forest Reserve and subjected to hydrodistillation in a Clevenger apparatus, and the essential oils obtained were analyzed using GC-FID and GC-MS. The essential oil of P. gallosum showed high percentages of oxygenated monoterpenes (43.61%) with a predominance of terpin-4-ol (25.15%), and P. paniculatum consisted exclusively of monoterpenes that were predominantly p-cymene (43.52%; hydrocarbon monoterpene) and the 1,8-cineole (16.83%; oxygenated monoterpene). Most of the monoterpenes identified from P. pillosum and P. paniculatum var. riedelianum were hydrocarbons with a predominance of α-pinene, with 37.74% and 50.93%, respectively. 1,8-Cineole (21.89%) was also identified in the essential oil of P. pillosum. The results obtained this study add chemical knowledge to Burseraceae resins from a biological reserve of the Central Amazon.